The Probable Critical Role of Early Holocene Monsoon Activity in Siting the Origins of Rice Agriculture in China - Dodson, John; Hung, Hsiao-chun; Li, Chenzi; Li, Jianyong; Lu, Fengyan; Yan, Hong (Frontiers in Earth Science, 2021)
The long process of rice domestication likely started 10,000 to 8000 years ago in China, and the pre-existing hunter-gatherer communities gradually adopted more sedentary lifestyles with the dependence of rice agricultural economies. The archaeological evidence builds a strong case for the first domestication of rice to Oryza sativa centred in the Middle-Lower Yangtze Valley during the early Holocene. The genetic evidence identifies the main ancestor of O. sativa was O. rufipogon, however, this now occurs naturally south of the Yangtze where its distribution is limited by summer temperatures and mean annual temperature. The mismatch between occurrence of ancestors and presumed sites of early cultivation leads to a number of hypotheses. These include that first domestication actually took place further south, such as in the Pearl River valley but archaeological evidence is currently lacking for this. Or domestication took place, when O. rufipogon had a more extensive natural range in the past. Early to mid-Holocene palaeoclimate reconstructions show that the East Asian Summer Monsoon was more active in the early Holocene and estimates show that the temperature requirements for O. rufipogon were met for a substantial area of northeast China at the time. This would mean that earliest known domestication sites and presumed ancestor distribution coincided for several millennia. Thus early records of rice farming in Henan and Shandong were easily accommodated by early to mid Holocene climates.